2018
DOI: 10.3390/app8112311
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene- and Propylene-Glycol Based Nanofluids: A Litterature Review on Their Thermophysical Properties and Thermal Performances

Abstract: Nanofluids are considered a promising way to improve the heat transfer capability of base fluids. Water is the most commonly-used heat transfer fluid. However, in refrigeration systems, it may be necessary to mix water with either ethylene- or propylene-glycol to lower its freezing point and prevent from ice formation. In the same way, for car radiators or industrial heat exchangers, the boiling point of water can be pushed up by mixing it with glycol-based fluids. The increasing awareness of energy saving and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 80 publications
0
31
0
Order By: Relevance
“…Or the final formula for calculating the turbulent viscosity of the coolant, taking into account the formula (6), is written in the form 9:…”
Section: Analysis Of the Forces Acting On The Nanoparticle Based On mentioning
confidence: 99%
See 1 more Smart Citation
“…Or the final formula for calculating the turbulent viscosity of the coolant, taking into account the formula (6), is written in the form 9:…”
Section: Analysis Of the Forces Acting On The Nanoparticle Based On mentioning
confidence: 99%
“…These include ethylene, propylene and di-propylene glycols of various concentrations in water. Also, nanofluids are widely used to increase the efficiency of heat exchange apparatuses as additives to heat carriers [6,7]. Some scientific works are devoted to mating combinations of various methods of enhancing heat transfer in heat exchangers, for example, using nanofluids simultaneously with spiral twists [8,9], using nanopowders with ethylene or propylene glycol additives to water [10].…”
Section: Introductionmentioning
confidence: 99%
“…Chiam et al [16] have developed correlations for the thermal conductivity and dynamic viscosity for Al 2 O 3 nanoparticles dispersed in water and EG mixtures with ratio of 40:60, 50:50 and 60:40 (by volume) as a function of nanoparticle concentration, temperature and nanoparticle diameter. Recently, Sekrani and Poncet [17] reviewed studies on the thermophysical properties and performances of EG or propylene-glycol (PG)-based nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the specific heat of the nanofluid was significantly enhanced by the presence of the graphite nanoparticles. G. Sekrani and S. Poncet [17] reviewed the possible use of ethylene-and propylene-glycol based nanofluids for applications in various thermal systems. These nanofluids can be applied by lowering the freezing point to prevent ice formation, such as in refrigeration systems, or pushing beyond the boiling point, such as in radiators or heat exchangers.…”
Section: Current Advances In the Applications Of Nanofluidsmentioning
confidence: 99%